(untitled) (Applied Biological Research, 2015)
The present study was aimed to find out the superiority amongst different use patterns in maize crop for higher yield, forage nutritional quality and profit. Three maize varieties each of baby corn, green cob, seed type and four forage type were grown together under field condition in kharif season 2011 and 2012. The mean green forage yield obtained from maize forage type was approximately 1.70 times higher than baby corn and seed type cultivars and 2 times than those of green cob type cultivars. The mean dry matter yield of forage type maize was 1.75, 1.60 and 1.35 times higher than baby corn, green cob and seed type, respectively. Forage type maize cultivar ‘African Tall’ gave significantly highest green forage yield, dry matter yield and crude protein yield. The highest mean per cent crude protein (8.5%), crude protein yield (7.38 q ha-1) and in vitro dry matter digestibility (58.7%) with the lowest mean crude fibre content (22.0%) and acid detergent fibre (43.0%) was observed in forage type maize. The lowest mean neutral detergent fibre (62.7%) and highest mean gross monetary returns, net monetary returns, B: C (3.5) and fodder equivalent yield was found in baby corn type maize cultivars. In conclusion, growing fodder type cultivars were suitable for producing more fodder yield with better nutritional quality; however, the baby corn type cultivars for earning the highest net profit along with fodder under limited land resources.